2013
DOI: 10.1007/s00244-013-9928-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity, Genotoxicity, and Estrogenic Activity of River Porewaters

Abstract: We investigated mutagenicity, genotoxicity, and estrogenic activity in the porewaters of two river basins in southern Italy that had different features. Three samples from each site were collected in different seasons from 7 sites for a total of 21 samples. Mutagenicity was measured with the Ames test with and without metabolic activation (S9) using Salmonella typhimurium TA98 and TA100 strains. Genotoxicity was measured with two tests: one involved a chromophore that detected DNA damage in Escherichia coli PQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…These results were consistent with the results obtained by analysis of fish bile extracts on field‐caught fish from the Xin'an River, which had lower EDC levels than the market sold fish in Shanghai. It has been reported that the estradiol equivalent values of surface water from some rivers in France range from 0.3 ng/L to 4.52 ng/L , ND to 3.1 ng/L in Italy , and 0.7 ng/L to 4.01 ng/L in Japan , similar to the results of water from the Xin'an River in the present study.…”
Section: Resultssupporting
confidence: 90%
“…These results were consistent with the results obtained by analysis of fish bile extracts on field‐caught fish from the Xin'an River, which had lower EDC levels than the market sold fish in Shanghai. It has been reported that the estradiol equivalent values of surface water from some rivers in France range from 0.3 ng/L to 4.52 ng/L , ND to 3.1 ng/L in Italy , and 0.7 ng/L to 4.01 ng/L in Japan , similar to the results of water from the Xin'an River in the present study.…”
Section: Resultssupporting
confidence: 90%
“…In Italy, tomatoes are mainly cultivated in the South especially in Agro Nocerino Sarnese (Campania Region) since it is one of the most fertile Italian flatlands for tomato production (31x10 6 This area is unfortunately affected by adverse environmental factors in relation to the Sarno River and its tributaries. The Sarno River is indeed, the most polluted river in Europe due to anthropogenic activity and uncontrolled industrial and urban waste disposal [8,9]. Many studies have shown that the Sarno river is contaminated by Potentially Toxic Elements (PTEs).…”
Section: Introductionmentioning
confidence: 99%
“…Montuori and co-authors [10] demonstrated that this river contributes to the pollution of the Tyrrhenian Sea with metals and polycyclic aromatic hydrocarbons (PHA). In a study conducted by Parrella et al [9], it is stated that the porewaters of the Sarno basin showed mutagenic/genotoxic effects. Recently, Cicchella and collaborators [11,12] demonstrated that Sarno stream sediments are contaminated with chromium (Cr) from tanneries and from copper (Cu) released from agricultural activities.…”
Section: Introductionmentioning
confidence: 99%
“…Xenobiotics deposited in sediments can cause cyto‐ and genotoxic effects in aquatic biota. Cyto‐ and genotoxicity of natural sediments can be estimated in elutriate‐ or extract‐based tests , but when toxicants are insoluble or present in the solid phase (like long‐lived natural and artificial radionuclides), whole‐sediment contact tests (such as the Allium test or tests similar to it) are more suitable . Aquatic plants rooted in sediments can be considered as potential indicators for estimating cyto‐ and genotoxicity in whole‐sediment contact tests, because they are used as in situ indicators of genotoxicity of natural bottom sediment.…”
Section: Introductionmentioning
confidence: 99%